2022
DOI: 10.3389/fonc.2022.940473
|View full text |Cite|
|
Sign up to set email alerts
|

Is liquid biopsy the future commutator of decision-making in liver transplantation for hepatocellular carcinoma?

Abstract: Liver transplant (LT) is the most favorable treatment option for patients with early stage hepatocellular carcinoma (HCC). Numerous attempts have been pursued to establish eligibility criteria and select HCC patients for LT, leading to various systems that essentially integrate clinico-morphological variables. Lacking of sufficient granularity to recapitulate the biological complexity of the disease, all these alternatives display substantial limitations and are thus undeniably imperfect. Liquid biopsy, define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…"Liquid biopsy" is promising tool in this regard, as it represents a minimally invasive approach to analyzing tumor components (cells or small pieces of DNA, RNA, or other molecules released by tumor cells) without need for tissue [43][44][45]. Liquid biopsy is dynamic and may be assessed at different peri-and post-LT time points [46].…”
Section: Recurrence Of Hepatocellular Carcinoma After Liver Transplan...mentioning
confidence: 99%
“…"Liquid biopsy" is promising tool in this regard, as it represents a minimally invasive approach to analyzing tumor components (cells or small pieces of DNA, RNA, or other molecules released by tumor cells) without need for tissue [43][44][45]. Liquid biopsy is dynamic and may be assessed at different peri-and post-LT time points [46].…”
Section: Recurrence Of Hepatocellular Carcinoma After Liver Transplan...mentioning
confidence: 99%
“…While two surgical methods, laparoscopic hepatectomy (LAP) and open hepatectomy (OPEN), are available, the 5-year survival rate of HCC patients remains low due to the high early recurrence rate. Research has demonstrated that recurrence after tumor resection and shorter recurrence-free survival are closely associated with circulating tumor cells (CTCS) ( 3 , 4 ). Consequently, assessing CTCS before and after radical hepatectomy is essential to improve the prognosis of HCC patients ( 5–8 ).…”
Section: Introductionmentioning
confidence: 99%
“…HCC is one of the most common malignancies around the world (1). The treatment of HCC is developing rapidly and includes hepatectomy, targeted system treatment, new internal and external radiotherapy technologies and liver transplantation (2). Radical hepatectomy remains the primary treatment for primary hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%